Research on the Application of Brand Design in Museum Cultural Products: -- Taking the "Dawu County Revolutionary Museum" Cultural and Creative Design as an Example - Du, Jialin (Transactions on Social Science, Education and Humanities Research, 2023)
In the 21st century, thanks to the selfless dedication of our forefathers, the life of the contemporary Chinese people has already achieved a prosperous country, a strong people, and a beautiful scene of prosperity in all aspects. In the contemporary prosperous environment, the material level to be satisfied, and then the pursuit of their own cultural accumulation, spiritual level of the sublimation. Among them with the red culture, red tourism with the combination of red, and IP into public view in our revolutionary red revolutionary spirit in our country in learning process, contemporary people have not only in retrospect, more is increasingly pay attention to learning and thinking, is how to put the red culture more specific, how to make the life and the culture of phase. Under the impetus of this development trend, Dawu county, which is located in the western end of the dabie mountain and has a history of glorious revolution, is also vigorously developing red cultural and creative products. Based on the old revolutionary base areas of Dawu important red culture on behalf of the revolutionary museum of Dawu county, Hubei province as study object and the status quo of the development of Dawu red text and design as the background, in this process, based on the local actual survey data, think about how to design, how to develop can also reflect the cultural characteristics and spirit of the red and the products. It strives to change the current situation that cultural and creative products in museums are single and homogenized after the integration of cultural and creative products and multiple elements.